2003
DOI: 10.1177/095965180321700405
|View full text |Cite
|
Sign up to set email alerts
|

Motion design and implementation for a hybrid drive system

Abstract: This paper presents a study of motion design and its implementation on a hybrid drive system that combines the motions of a large constant speed motor with a small servo motor by means of a mechanism in order to provide a powerful programmable drive system. In general, the most suitable function used to generate motion curves is the power form of polynomial functions. However, this function may produce some unexpected oscillations between the boundary conditions. A methodology is given to prevent this drawback… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The mathematics involved while deriving the equations of motion is included in reference [4]. Here they are all taken from the previous work and arranged as follows.…”
Section: Equations For the Mechanism And The Actuatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mathematics involved while deriving the equations of motion is included in reference [4]. Here they are all taken from the previous work and arranged as follows.…”
Section: Equations For the Mechanism And The Actuatorsmentioning
confidence: 99%
“…The equations describing the dynamic behaviour of the motors include the armatures electrical and the dynamic equation. Seven link mechanism referred in this study [3,4] The electrical equation of a BLDC and a PMDC [16] is…”
Section: Equations For the Mechanism And The Actuatorsmentioning
confidence: 99%
“…The optimized design showed that theoretical savings of 70 per cent in peak servo motor power could be achieved with the hybrid concept compared to a direct drive case in which the servo motor provided the required motions directly. A general method for the design of motion trajectories and its implementation in an experimental hybrid machine has recently been reported [4].…”
Section: Introductionmentioning
confidence: 99%